Improving Procurement Process Management by Application of KPIs in the Company from Metal Industry - Đukanović, Sandra; Lečić-Cvetković, Danica; Rajković, Teodora (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The procurement process is one of the most critical processes for any company, as it ensures the provision of all necessary material resources. Improving the procurement process can contribute to reducing procurement costs by acquiring higher-quality raw materials, shortening delivery time, producing higher-quality products, and enhancing business relationships with suppliers. The subject of this paper is the improvement of the procurement process management, based on Key Performance Indicators (KPIs). The paper presents a set of five KPIs defined and implemented in the procurement process management on a case study of a real company from the metal industry. The result of the application of selected KPIs is improved procurement process that observed company use for monitoring supplier performance and the procurement department's efficiency. It also led to the applications of corrective measures, such as contract revision and modification, or termination of partnerships in favor of more reliable suppliers, as well as enhanced efficiency in the operations of the procurement department.